2005
DOI: 10.1007/s00702-005-0342-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of non-verbal semantic sound processing in humans

Abstract: Environmental sounds convey specific meanings and the neural circuitry for their recognition may have preceded language. To dissociate semantic mnemonic from sensory perceptual processing of non-verbal sound stimuli we systematically altered the inherent semantic properties of non-verbal sounds from natural and man-made sources while keeping their acoustic characteristics closely matched. We hypothesized that acoustic analysis of complex non-verbal sounds would be right lateralized in auditory cortex regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…The left amygdala emerged as a region that shows greater BOLD activity to emotional relative to neutral stimuli at probe onset and during target set presentation, suggesting that this region may be involved in processing emotional information at encoding in this task. This finding is consistent not only with prior research that has shown that the amygdala is central for processing emotional information and task relevance (Sander, Grafman, & Zalla, 2003;Phelps, LaBar, & Spencer, 1998;LeDoux, 1996) but also with research that has shown that the left amygdala, in particular, processes emotional verbal information (Engelien et al, 2006;Isenberg et al, 1999). On the basis of the present set of findings, we cannot conclude what the role of the left amygdala may have in the emotional facilitation of interference resolution.…”
Section: Discussionsupporting
confidence: 82%
“…The left amygdala emerged as a region that shows greater BOLD activity to emotional relative to neutral stimuli at probe onset and during target set presentation, suggesting that this region may be involved in processing emotional information at encoding in this task. This finding is consistent not only with prior research that has shown that the amygdala is central for processing emotional information and task relevance (Sander, Grafman, & Zalla, 2003;Phelps, LaBar, & Spencer, 1998;LeDoux, 1996) but also with research that has shown that the left amygdala, in particular, processes emotional verbal information (Engelien et al, 2006;Isenberg et al, 1999). On the basis of the present set of findings, we cannot conclude what the role of the left amygdala may have in the emotional facilitation of interference resolution.…”
Section: Discussionsupporting
confidence: 82%
“…Processing nonverbal sounds does not require any linguistic knowledge, whereas (depending on the complexity of the speech production) comprehension of spoken language requires recognition of phonological, syntactical, lexical, and/or semantic features. Moreover, nonverbal or environmental sounds are considered to convey specific meanings, and the neural circuitry for their recognition may precede the earliest stages of language development (Engelien et al, 2006). The impact of exposure to nonlinguistic sound stimuli on the development of cognitive and communication abilities of children with CP requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…tools, animals, liquids, dropped objects) and nonmeaningful sounds (such as reversed sounds) both activate bilateral posterior and middle STS (pSTS and mSTS) (Lewis et al, 2004(Lewis et al, , 2005. However, meaningful sounds show a left lateralization when compared to non-meaningful sounds (Engelien et al, 2006;Lewis et al, 2004). Within the category of meaningful sounds, those that are human voice-specific (i.e.…”
Section: The Sts and Language Functionsmentioning
confidence: 97%